Etude des effets de la sélection sur les gènes de l'amylase chez une population d'huître creuse Crassostrea gigas en fonction des conditions trophiques précoces - Sauvage, Christopher (2003)
In natural population of the Pacific cupped oyster, there are differences between allelic and genotypic frequencies for the A and B amylase genes. Set up a synthetical population of C. gigas, in which whole alleles and genotypes are better represented than in wild population, was done. An investigation links between trophic conditions applied during larvae developpment (in nursery), allelic frequencies for both amylase genes, oyster's individual waight and by the selectivity of summer mortalities during their exposition on the estran has been done. As a result, following facts have been observed : - On one side, an influence of the trophic condition applied during the larvae development on genotypic frequencies of the gene B of the amylase - On the other side, there is a link between the phenotype and the genotype. Then, comparison of genotypic frequencies obtained in march and september 2002, allowed us to highlight the weak sensibility of the marker amylase in the study of the selective pressure exercised by the phenomenon of summer mortalities. Au sein de populations naturelles d'huîtres creuses, il existe des différences entre les fréquences alléliques et génotypiques sur les gènes A et B de l'amylase. La constitution d'une population synthétique de C. gigas où l'ensemble des allèles et génotypes sont représentés dans de meilleures proportions que dans les populations naturelles a été effectuée. Une recherche des liens entre les conditions trophiques appliquées en élevage larvaire (en nurserie), les fréquences alléliques pour ces deux gène de l'amylase, le poids individuel des huîtres et la sélectivité par les mortalités estivales lors de leur exposition sur estran a été entreprise. En résultat, les faits suivants ont été observés : - d'une part, une influence de la condition trophique appliquée lors de l'élevage larvaire sur les fréquences génotypiques pour le gène B de l'amylase - d'autre part qu'il existe un lien certain entre le phénotype d'un individu et son génotype (lien fréquence génotypique - ...